Respostas
respondido por:
1
Temos que:
x = 11 - y
Substituindo na segunda equação temos:
(11 - y) - y = 5
11 -2y = 5
-2y = 5 - 11
-2y = -6
y = 3
x = 11 - y
x = 11 - 3
x = 8
x = 11 - y
Substituindo na segunda equação temos:
(11 - y) - y = 5
11 -2y = 5
-2y = 5 - 11
-2y = -6
y = 3
x = 11 - y
x = 11 - 3
x = 8
respondido por:
0
x = 11-y
x-y= 5
11-y-y = 5
-2y = 5-11
-2y = -6 (.-1)
2y = 6
y = 6/2
y = 3
x+y = 11
x+3= 11
x = 11-3
x = 8
(8,3)
x-y= 5
11-y-y = 5
-2y = 5-11
-2y = -6 (.-1)
2y = 6
y = 6/2
y = 3
x+y = 11
x+3= 11
x = 11-3
x = 8
(8,3)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás